Sistem Informasi Penjualan Barang pada Toko Listrik Tiga Dara Berbasis Android - Alda, Muhamad; Rahma, Baqiyatur; Pramesti, Adinda Ayu Mega; Silalahi, Nurul Ifkah Lolona (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Tiga Dara Electrical Shop is a shop that sells various kinds of electrical equipment such as plugs, electrical tools, light fittings, power cords, light switches, fans, lamps and remotes. In line with this, orders for goods at Tiga Dara Electrical Shop continue to grow. One of the activities that everyone always does to meet their needs every day is to shop. The more developed technology nowadays, it can be done anytime and anywhere. ordering goods. The goods sales information system has 2 types of users, namely users and shop owners who serve as account holders (admin). The expected results with this application can make it easier for customers to place orders, and so on. Keywords: Tiga Dara Electrical Shop, Sales Information System, Android